Henry M. Stanley correspondence - Stanley, Henry M. (Henry Morton), 1841-1904.
ALS (1878 October 10; London) to Elizabeth S. Stevens and ALS (1879 January 12; London) to a Mr. Whiting. Both letters are of a social nature.
British explorer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Stevens, Elizabeth S. -- Correspondence; Whiting, -- Mr. -- Correspondence; Explorers